Corrosion of Q235 carbon steel induced by sulfate-reducing bacteria in groundwater: corrosion behavior, corrosion product, and microbial community structure - Wenxin Hua; Rui Sun; Xiaoyan Wang; Yunyun Zhang; Jiaxing Li; Ri Qiu; Yu Gao (Environmental Science and Pollution Research, 2023)

Effect of vane angle on turbulence–chemistry interactions, temperature, flow field, burnout, and NOx emissions in swirling flames fueled by semicoke mixtures - Liutao Sun; Shengyu Kuang; Weilin Li; Jingjie Wang; Yanhui Xu; Lingkun Zhu; Hong Tian; Xinzhuo Li; Dengke Wang; Rui Sun (Environmental Science and Pollution Research, 2023)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Carbon-neutral potential in treatment of N, N-dimethylformamide-containing industrial wastewater: Comparative investigation of energy conservation, carbon reduction and expenditure between UASB and Fenton process - Xinwei Tan; Yuqin Fan; Xinzheng Zhang; Tianwei Hao; Rong Chen; Tao Zhang; Rui Lu; Jianliang Sun; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2023)

Preparation of super hydrophilic-underwater super oleophobic photoinduced self-cleaning Al2O3 @TiO2 ceramic membrane and separation performance of oil-in-water emulsion - Dongdong Wang; Likun Huang; Xinyi Miao; Xiyu Sun; Simin Zhou; Rui Zhao; Guangzhi Wang; Haiyang Sun; Shaofang Li; Zhe Li (Journal of Environmental Chemical Engineering, 2023)

Significant methane ebullition from large shallow eutrophic lakes of the semi-arid region of northern China - Linxiang Zhang; Xiangwei Li; Ruihong Yu; Yue Geng; Liangqi Sun; Heyang Sun; Yuan Li; Zhonghua Zhang; Xiangyu Zhang; Xue Lei; Rui Wang; Changwei Lu; et al. (Journal of Environmental Management, 2023)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Combining vegetation, color, and texture indices with hyperspectral parameters using machine-learning methods to estimate nitrogen concentration in rice stems and leaves - Dunliang Wang; Rui Li; Tao Liu; Shengping Liu; Chengming Sun; Wenshan Guo (Field Crops Research, 2023)

Characteristics of dissolved organic matter in point-source wastewaters at a petrochemical plant: Molecular constituents and contributions to the influent of wastewater treatment plant - Yue Kou; Baiyu Yang; Juntao Jiang; He Sun; Rui Zhang; Zhuoyu Li; Qinghong Wang; Quan Shi; Chunmao Chen (Environmental Research, 2023)

Sulfide-modified nanozerovalent iron for rapid decontamination of Cu(Ⅱ) complexes in high-salinity wastewater - Rui Li; Xiaozhi Wang; Xiuyun Sun; Jiansheng Li; Jinyou Shen (Environmental Pollution, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

Improvement of Soil Structure and Bacterial Composition by Long-Term Application of Seaweed Fertilizer - Liu Qiqin; Zhou Huaguang; Sun Minxiu; Li Qian; Fan Haijun; Chen Haimin; Yang Rui (Journal of Soil Science and Plant Nutrition, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Acylhydrazone Functionalized Triphenylamine-Based Fluorescent Probe for Cu2+: Tunable Structures of Conjugated Bridge and Its Practical Application - Xiaohong Cheng; Rui Zhang; Jinbo Sun; Ke Xu; Wangnan Li (Journal of Fluorescence, 2023)

Biochar-derived dissolved organic matter (BDOM) and its influence on soil microbial community composition, function, and activity: A review - Muhammad Azeem; Tian-Ran Sun; Parimala Gnana Soundari Arockiam Jeyasundar; Rui-Xia Han; Hui Li; Hamada Abdelrahman; Sabry M. Shaheen; Yong-Guan Zhu; Gang Li (Critical Reviews in Environmental Science and Technology, 2023)

Aluminum soap nanoparticles-lignin powder form phase-selective gelator as an efficient sorbent for oils/water separation - Suwan Cui; Bohao Qi; Hao Liu; Xiaojun Sun; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Mutai Bao (Chemosphere, 2023)

Whole-genome analysis of the benzoic acid-degrading bacterium Bacillus halotolerans B28 to reveal its phytoprobiotic effects - Dandan Wang; Li Sun; Hong Yu; Chengkai Zhang; Xin Guan; Mengliang Wang; Rui Cheng; Chao Wang; Zhihong Xie (International Biodeterioration & Biodegradation, 2023)

Hydrophobic aggregation via partial Gal removal affects solution characteristics and fine structure of tamarind kernel polysaccharides - Rui Guo; Xianbao Sun; Yuxing Kou; Hong Song; Xujiao Li; Lihua Song; Taolei Zhao; Hui Zhang; Deshun Li; Yanfang Liu; Zibo Song; Jieli Wu; et al. (Food Hydrocolloids, 2023)

Efficient antibiotic wastewater treatment via interfacial water evaporation based soot-coated conjugated microporous polymer hollow microspheres - Wenwen Luo; Meichen Liu; Rui Jiao; Yunjia Wang; Jiyan Li; Zhaoqi Zhu; Weidong Liang; Hanxue Sun; An Li (Chemical Engineering Journal, 2023)

Enhancing biomass oxidation with carbon nitride nanosheets ring inserted on C. I. Pigment Yellow 53 photocatalysts for simultaneous CO and lactic acid production - Weikang Ling; Jiliang Ma; Zhendong Liu; Rui Cui; Junqiang Zhang; Xinze Li; Min Hong; Runcang Sun (Chemical Engineering Journal, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

Fruit detachment force of multiple varieties kiwifruit with different fruit-stem angles for designing universal robotic picking end-effector - Wentai Fang; Zhenchao Wu; Weiwu Li; Xiaoming Sun; Wulan Mao; Rui Li; Yaqoob Majeed; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Twice matched fruit counting system: An automatic fruit counting pipeline in modern apple orchard using mutual and secondary matches - Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Fangfang Gao; Rui Li; Longsheng Fu; Dong Zhang; Spyros Fountas (Biosystems Engineering, 2023)

Analysis of the contribution of land consolidation to sustainable poverty alleviation under various natural conditions - Hanbing Li; Xiaobin Jin; Barbara Prack McCormick; Pablo Tittonell; Jing Liu; Bo Han; Rui Sun; Yinkang Zhou (Land Use Policy, 2023)

Enhanced nitrogen removal in a pilot-scale AOA-SBFASR system treating municipal wastewater: Process efficiency, microbial community and nitrogen metabolic pathways - Zhi-li Du; Shao-bin Huang; Rui-jian Zhang; Yong-qing Zhang; Hao-tao Dong; Guang-hua Wang; Zhi-min Sun (Journal of Water Process Engineering, 2023)

Membrane flux response technology for early warning of initial surface scaling in membrane distillation - Zhijie Yuan; Rui Zhao; Guoxin Sun; Peiyu Li; Shaohua Yin; Guoli Zhou; Gaohong He; Xiaobin Jiang (Journal of Water Process Engineering, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Nano-agriculture and nitrogen cycling: Opportunities and challenges for sustainable farming - Quanlong Wang; Li Gao; Yuanbo Li; Noman Shakoor; Yi Sun; Yaqi Jiang; Guikai Zhu; Fayuan Wang; Yunze Shen; Yukui Rui; Peng Zhang (Journal of Cleaner Production, 2023)

Surface modification of PVDF membranes with quaternized chitosan for selective separation of negatively charged polysaccharides – exemplified with heparin - Rui Zhang; Yahong Li; Jingjing Yan; Jianxian Zeng; Yuan Liu; Mingming Zhang; Pengfei Liu; Xiaoping Huang; Erdong Zhang; Kaipeng Cheng; Jingyu Chen; Jialin Sun (Journal of Environmental Chemical Engineering, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

Laboratory acousto-mechanical study into moisture-induced changes of elastic properties in intact granite - Rui Wu; Paul Antony Selvadurai; Ying Li; Yongyang Sun; Kerry Leith; Simon Loew (International Journal of Rock Mechanics and Mining Sciences, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

Dual network hydrogel coatings based on recombinant mussel protein with enhanced antibacterial and super-lubrication properties for urinary catheter applications - Yubo Hu; Youzhi Qiao; Peng Lei; Yian Gu; Liang Sun; Yibin Qiu; Sha Li; Hong Xu; Rui Wang (Chemical Engineering Journal, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Flat-leaf submerged plants are more sensitive to invasion intensity and water nutrition levels than needle-leaf ones - Yi-Luan Shen; Shu-Yu Zhang; Xiao-Fei Yuan; Kai Sun; Jing-Fang Cai; Jing-Jing Xue; Yu Zhang; Si-Ha A; Li-Juan Yang; Rui Cheng; Hong-Li Li; Guang-Chun Lei (Hydrobiologia, 2023)

Development of a novel fluorescent aptasensor based on the interaction between hexagonal β-Co(OH)2 nanoplates and nitrogen-doped carbon dots for ultrasensitive detection of patulin - Qi Sun; Zhijuan Li; Ningxin Liu; Yuting Zhou; Fuyan Zhang; Shuang Li; Peng Jin; Rui Xiang; Tao Le (Analytica Chimica Acta, 2023)

Effects of Snail Bellamya purificata Farming at Different Stocking Densities on the Algal and Fungal Communities in Sediment - Yiran Hou; Mengmeng Zhou; Rui Jia; Wei Sun; Yanhong Yang; Xiongjian Huang; Bing Li; Jian Zhu (Fishes, 2023)
The snail Bellamya purificata is recognized as a potential bio-remediation species, and is commonly employed in polyculture to enhance resource utilization efficiency and realize culture environment regulation. In order to enrich the microbiome studies on elucidating the ecological effects of snail B. purificata farming, we assessed the effect of B. purificata farming activities, at varying stocking densities, on the algal and fungal communities in sediment. Four experimental groups were established in our study, each corresponding to a different stocking density: 0, 234.38, 468.75, and 937.5 g/m2, represented as CON, LD, MD, and HD, respectively. High-throughput sequencing based on ITS and 23S ribosomal RNA (rRNA) genes was employed to analyze the variations in algal and fungal communities under B. purificata farming activities at different stocking densities. B. purificata farming activities had no significant effect on the alpha diversities of fungal and algal communities, but significantly altered the compositions of fungal and algal communities in sediments, especially B. purificata farming activity at low stocking density. B. purificata farming activities at low stocking density could significantly increase the relative abundances of fungal genera Paraconiothyrium and Penicillium compared with the CON group. The promoting effect diminished with increasing density. B. purificata farming activities at low or medium stocking density also could enhance the relative abundances of algal genera Microchloropsis, Scenedesmus, and Auxenochlorella. Hence, B. purificata farming activity at low stocking density might be the optimum density to enhance resource utilization efficiency and minimize environmental pollution.

Study on the correlation and interaction between metals and dyslipidemia: a case–control study in Chinese community-dwelling elderly - Zhongyuan Zhang; Rui Wang; Pei He; Yuqing Dai; Siyu Duan; Meiyan Li; Zhuoheng Shen; Xiaoyu Li; Jian Sun (Environmental Science and Pollution Research, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

Understanding land-use sustainability with a systematical framework: An evaluation case of China - Bo Han; Xiaobin Jin; Rui Sun; Hanbing Li; Xinyuan Liang; Yinkang Zhou (Land Use Policy, 2023)

Anaerobic selenite-reducing bacteria and their metabolic potentials in Se-rich sediment revealed by the combination of DNA-stable isotope probing, metagenomic binning, and metatranscriptomics - Rui Xu; Max Kolton; Wan Tao; Xiaoxu Sun; Pingzhou Su; Duanyi Huang; Miaomiao Zhang; Zhaohui Yang; Zhaohui Guo; Hanbing Gao; Qi Wang; Baoqin Li; et al. (Journal of Hazardous Materials, 2023)

Characterizing VOCs emissions of five packaging and printing enterprises in China and the emission reduction potential of this industry - Guiying You; Hefan Liu; Rui Sun; Zengxin Jin; Jing Li; Xiaoling Zhou; Sihua Lu; Shaodong Xie (Journal of Cleaner Production, 2023)

Structure, rheology, and antifreeze property of the exopolysaccharide from Naematelia aurantialba through basidiospore fermentation - Tao Sun; Xiaoyi Xu; Yuhang Ma; Hao jiang; Kai Yang; Rui Wang; Yian Gu; Sha Li; Yibin Qiu; Dafeng Sun; Hong Xu; Peng Lei (Food Hydrocolloids, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Remarkable bioactivity, bio-tribological, antibacterial, and anti-corrosion properties in a Ti-6Al-4V-xCu alloy by laser powder bed fusion for superior biomedical implant applications - Jiang Ju; Rui Zan; Zhao Shen; Chenchen Wang; Peng Peng; Jun Wang; Baode Sun; Bo Xiao; Qian Li; Shaofei Liu; Tao Yang (Chemical Engineering Journal, 2023)

Boosted photogenerated charge carrier separation by synergy of oxygen and phosphorus co-doping of graphitic carbon nitride for efficient 2-chlorophenol photocatalytic degradation - Zhuzhu Zhang; Qimeng Sun; Rui Ji; Dongyun Chen; Najun Li; Hua Li; Qingfeng Xu; Huilong Dong; Jianmei Lu (Chemical Engineering Journal, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

The biocontrol agent Bacillus velezensis T-5 changes the soil bacterial community composition by affecting the tomato root exudate profile - Yian Gu; Weina Liang; Zhidan Li; Sijie Liu; Sun Liang; Peng Lei; Rui Wang; Nan Gao; Sha Li; Zongqi Xu; Hong Xu (Plant and Soil, 2023)

Development and validation a prognostic model based on natural killer T cells marker genes for predicting prognosis and characterizing immune status in glioblastoma through integrated analysis of single-cell and bulk RNA sequencing - Jiahe Hu; Lei Xu; Wenchao Fu; Yanan Sun; Nan Wang; Jiheng Zhang; Chengyun Yang; Xiaoling Zhang; Yuxin Zhou; Rongfang Wang; Haoxin Zhang; Ruishu Mou; et al. (Functional & Integrative Genomics, 2023)

Do not ignore the effects of phosphorus and potassium addition on microbial carbon use efficiency - Chenyang Zhang; Liyang Sun; Yichao Rui; Yue Li; Yiqi Luo; Minggang Xu; Andong Cai (Global Change Biology, 2023)

NDMFCS: An automatic fruit counting system in modern apple orchard using abatement of abnormal fruit detection - Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Wulan Mao; Rui Li; Nikita Andriyanov; Vladimir Soloviev; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

The potential of biochar as a microbial carrier for agricultural and environmental applications - Shiv Bolan; Deyi Hou; Liuwei Wang; Lauren Hale; Dilfuza Egamberdieva; Priit Tammeorg; Rui Li; Bing Wang; Jiaping Xu; Ting Wang; Hongwen Sun; Lokesh P. Padhye; et al. (Science of The Total Environment, 2023)

A method to estimate leaf area index from VIIRS surface reflectance using deep transfer learning - Juan Li; Zhiqiang Xiao; Rui Sun; Jinling Song (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Physicochemical properties and in vitro digestion behavior of emulsion gels stabilized by rice bran protein aggregates: Effects of heating time and induction methods - Yongxue Luo; Kexin Wang; Rui Pan; Ting Li; Qingjie Sun; Chuanfen Pu; Wenting Tang (Food Research International, 2023)

A spike-trimer protein-based tetravalent COVID-19 vaccine elicits enhanced breadth of neutralization against SARS-CoV-2 Omicron subvariants and other variants - Rui Wang; Hongpeng Huang; Chulin Yu; Chunyun Sun; Juan Ma; Desheng Kong; Yalong Lin; Dandan Zhao; Shaozheng Zhou; Jianbo Lu; Sai Cao; Yanjing Zhang; et al. (Science China Life Sciences, 2023)

Second-order accurate implicit finite volume method for two-dimensional modeling of PFAS transport in unsaturated porous media with variable surface tension - Rui Wu; Xiaoxing Li; Yuanyuan Sun; Piotr Szymczak; Wentao Jiao (Advances in Water Resources, 2023)

Selective CDK9 knockdown sensitizes TRAIL response by suppression of antiapoptotic factors and NF-kappaB pathway - Qian Yuan; Kui Su; Shuyi Li; Xinyi Long; Lang Liu; Jianwu Sun; Xin Yuan; Minghui Yang; Rui Tian; Wanting Zhang; Zhujie Deng; Quanjiang Li; et al. (Apoptosis, 2023)

Screening eco-friendliness tire antioxidants alternatives: functional 2,2,4-trimethyl-1,2-dihydroquinoline derivatives design and toxicity evaluation - Yu Wang; Rui Fu; Peixuan Sun; Xinao Li; Wenjin Zhao (Environmental Science and Pollution Research, 2023)

Performance of Zeolite and Trace Elements on Biogas Production from Alkaline Hydrogen Peroxide–Pretreated Sweet Sorghum Bagasse Slurry - Xuemei Li; Ying Xiao; Rui Zhang; Chen Sun; Weixing Cao (BioEnergy Research, 2023)

Resistivity responses of sodium sulfate and sodium chloride-type loess under different water and salinity conditions - Xiaoran Li; Qiang Sun; Xusheng Yan; Pengfei Li; Rui Lv (Environmental Science and Pollution Research, 2023)

Precipitation variations in arid central Asia over past 2500 years: Possible effects of climate change on development of Silk Road civilization - Guoqiang Ding; Jianhui Chen; Yanbin Lei; Feiya Lv; Rui Ma; Shengqian Chen; Shuai Ma; Yuanhao Sun; Yuecong Li; Haipeng Wang; Zhilin Shi; Heikki Seppä; et al. (Global and Planetary Change, 2023)

Plasmon driven super-high HER activity of electronic structure and lattice strain engineered single atomic layer Pd@Au nanorods - Yi-Bai Sun; Miao Ni; Chen Chi; Dong-Rui Yang; Xue-Lu Chen; Qi Qi; Jian Li; Xing-Hua Xia (Chemical Engineering Journal, 2023)

ROS and DRP1 interactions accelerate the mitochondrial injury induced by polystyrene nanoplastics in human liver HepG2 cells - Yunjing Li; Menghao Guo; Shuyan Niu; Mengting Shang; Xiaoru Chang; Zuoyi Sun; Rui Zhang; Xin Shen; Yuying Xue (Chemico-Biological Interactions, 2023)

Removal of toilet paper fibers from residential wastewater: a life cycle assessment - Xiaoyu Wang; Guoqiang Liu; Weimin Sun; Zhiguo Cao; Huaqing Liu; Yiqun Xiong; Baoqin Li; Xiaoxu Sun; Yongbin Li; Rui Xu; Duanyi Huang; Pin Gao (Environmental Science and Pollution Research, 2023)

Thin wire segmentation and reconstruction based on a novel image overlap-partitioning and stitching algorithm in apple fruiting wall architecture for robotic picking - Hanhui Jiang; Xiaoming Sun; Wentai Fang; Longsheng Fu; Rui Li; Fernando Auat Cheein; Yaqoob Majeed (Computers and Electronics in Agriculture, 2023)

Phenotyping of individual apple tree in modern orchard with novel smartphone-based heterogeneous binocular vision and YOLOv5s - Guanao Zhao; Ruizhe Yang; Xudong Jing; Haosen Zhang; Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Rui Li; Xiaofeng Wei; Spyros Fountas; Huijun Zhang; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Insight into micropollutant abatement during ultraviolet light-emitting diode combined electrochemical process: Reaction mechanism, contributions of reactive species and degradation routes - Rui Hu; Sui-Qin Yang; Jia-Ying Li; Fengyi Sun; Zheng-Qian Liu; Jingjing Yang; Yu-Hong Cui; Beiping Zhang (Science of The Total Environment, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

A Responsive Feeding Questionnaire Based on Self-Determination Theory for Caregivers of Chinese Toddlers - Yan Liu; Guiling Yu; Zhihui Li; Yan Kong; Rui Yang; Chunlan Yin; Xiaodi Sun (Journal of Nutrition Education and Behavior, 2023)

Nanoencapsulation-based fabrication of eco-friendly pH-responsive pyraclostrobin formulations with enhanced photostability and adhesion to leaves - Yingjian Ma; Linjie Li; Rui Zhao; Zhe Sun; Yinmin Wang; Meng Yu; Shouhe Pan; Xinyu Guo; Yong Xu; Hongmei Wang; Ping Wang; Xuemin Wu (Journal of Environmental Chemical Engineering, 2023)

Solid-state fermentation alters the fate of red kidney bean protein during buccal and gastrointestinal digestion: Relationship with cotyledon cell wall integrity - Wenjing Sun; Jie He; Haijun Wang; Qiuqin Zhang; Wei Li; Xin Rui (Food Chemistry, 2023)

Complete nitrogen removal from low-strength wastewater via double nitrite shunt coupling anammox and endogenous nitrate respiration: Functional metabolism and electron transport - Qiongpeng Dan; Rui Du; Tong Wang; Tiantian Sun; Honggui Han; Xiaorong Zhu; Xiyao Li; Qiong Zhang; Yongzhen Peng (Chemical Engineering Journal, 2023)

Internet addiction-induced brain structure and function alterations: a systematic review and meta-analysis of voxel-based morphometry and resting-state functional connectivity studies - Jing-Ting Sun; Bo Hu; Tian-Qi Chen; Zhu-Hong Chen; Yu-Xuan Shang; Yu-Ting Li; Rui Wang; Wen Wang (Brain Imaging and Behavior, 2023)

Experimental study on the movement law of overlying rock non-pillar coal overhead mining - Yong Li; Jing Zheng; Feng-nian Wang; Xin-gen Ma; Rui-xue Zhang; Ying-ying Sun; Jian-bin Yin; Zhi-gang Tao (Journal of Mountain Science, 2023)

Porcine Mx proteins inhibit pseudorabies virus replication through interfering with early gene synthesis - Jing Chen; Jia-huan Hu; Rui-cong Sun; Xiao-han Li; Jing Zhou; Bin Zhou (Veterinary Microbiology, 2023)

A quasi-one-dimensional bulk thermoelectrics with high performance near room temperature - Qingxin Dong; Junsen Xiang; Zhen Wang; Yunxiu Li; Rui Lu; Te Zhang; Nan Chen; Yifei Huang; Yiyan Wang; Wenliang Zhu; Guodong Li; Huaizhou Zhao; et al. (Science Bulletin, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Emerging trends in pectin functional processing and its fortification for synbiotics: A review - Rui Sun; Yefan Niu; Menghui Li; Yuanye Liu; Kai Wang; Zhenpeng Gao; Zhouli Wang; Tianli Yue; Yahong Yuan (Trends in Food Science & Technology, 2023)

Introduction of multilayered magnetic core–dual shell SERS tags into lateral flow immunoassay: A highly stable and sensitive method for the simultaneous detection of multiple veterinary drugs in complex samples - Jian Tu; Ting Wu; Qing Yu; Jiaxuan Li; Shuai Zheng; Kezong Qi; Guohui Sun; Rui Xiao; Chongwen Wang (Journal of Hazardous Materials, 2023)

Preparation of CeVO4/BNNS catalyst and its application in oxidation desulfurization of diesel oil - Xinyu Li; Junjun Shi; Jiangang Wang; Lei Xi; Rui Sun; Fan Zhang; Xi Wu; Zhiyong Zhou; Zhongqi Ren (Fuel, 2023)

The interaction mechanism and the functionality of yeast protein with hydrophilic and hydrophobic bioactive molecules - Haili Sun; Yifei Sun; Xin Tang; Yuanmeng Cui; Demei Meng; Yuyu Zhang; Ku Li; Hui Guo; Hai Chen; Rui Yang (Food Bioscience, 2023)

Long-term exposure to fine particulate matter and site-specific cancer mortality: A difference-in-differences analysis in Jiangsu province, China - Zhaoyu Fan; Yingxin Li; Jing Wei; Gongbo Chen; Rui Wang; Ruijun Xu; Tingting Liu; Ziquan Lv; Suli Huang; Hong Sun; Yuewei Liu (Environmental Research, 2023)

Boosting photocatalytic ammonia synthesis performance over OVs-Rich Ru/W18O49: Insights into the roles of oxygen vacancies in enhanced hydrogen spillover effect - Lulu Zhang; Rui Li; Luyao Cui; Zijun Sun; Lijun Guo; Xiaochao Zhang; Yunfang Wang; Yawen Wang; Zhuobin Yu; Tao Lei; Xuan Jian; Xiaoming Gao; et al. (Chemical Engineering Journal, 2023)

In-situ sensor calibration for building HVAC systems with limited information using general regression improved Bayesian inference - Guannan Li; Jiahao Xiong; Rui Tang; Shaobo Sun; Chongchong Wang (Building and Environment, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Fast and visual detection of nucleic acids using a one-step RPA-CRISPR detection (ORCD) system unrestricted by the PAM - Kangfeng Lin; Jianguang Guo; Xiangju Guo; Qinghan Li; Xiao Li; Zhen Sun; Zehang Zhao; Jiao Weng; Jinzhun Wu; Rui Zhang; Boan Li (Analytica Chimica Acta, 2023)

Species of fast bulk‐soil nutrient cycling have lower rhizosphere effects: A nutrient spectrum of rhizosphere effects - Lijuan Sun; Yuki Tsujii; Tianle Xu; Mengguang Han; Rui Li; Yunfeng Han; Dayong Gan; Biao Zhu (Ecology, 2023)
Tree roots not only acquire readily‐usable soil nutrients but also affect microbial decomposition and manipulate nutrient availability in their surrounding soils, that is, rhizosphere effects (REs). Thus, REs challenge the basic understanding of how plants adapt to the environment and co‐exist with other species. Yet, how REs vary among species in response to species‐specific bulk soil nutrient cycling is not well‐known. Here, we studied how plant‐controlled microbial decomposition activities in rhizosphere soils respond to those in their corresponding bulk soils and whether these relations depend on species‐specific nutrient cycling in the bulk soils. We targeted 55 woody species of different clades and mycorrhizal types in three contrasting biomes, namely a temperate forest, a subtropical forest, and a tropical forest. We found that microbial decomposition activities in rhizosphere soils responded linearly to those in their corresponding bulk soils at the species level. Thereafter, we found that REs (parameters in rhizosphere soils minus those in corresponding bulk soils) of microbial decomposition activities had negative linear correlations with microbial decomposition activities in corresponding bulk soils. A multiple factor analysis revealed that soil organic carbon, total nitrogen, and soil water content favored bulk soil decomposition activities in all three biomes, showing that the magnitude of REs varied along a fast‐slow nutrient cycling spectrum in bulk soils. The species of fast nutrient cycling in their bulk soils tended to have smaller or even negative REs. Therefore, woody plants commonly utilize both positive and negative REs as a nutrient‐acquisition strategy. Based on the trade‐offs between REs and other nutrient‐acquisition strategies, we proposed a push and pull conceptual model which can bring plant nutrient‐acquisition cost and plant carbon economics spectrum together in the future. This model will facilitate not only the carbon and nutrient cycling but also the mechanisms of species co‐existence in forest ecosystems.

Assessment of dynamic digestion fate of soy protein gel induced by lactic acid bacteria: A protein digestomics research - Yaqiong Wang; Wenjing Sun; Yi Zhang; Wei Li; Qiuqin Zhang; Xin Rui (Food Hydrocolloids, 2023)

Biotransformation of bisphenol A in vivo and in vitro by laccase-producing Trametes hirsuta La-7: Kinetics, products, and mechanisms - Jie Liu; Kai Sun; Rui Zhu; Xun Wang; Michael Gatheru Waigi; Shunyao Li (Environmental Pollution, 2023)

Molecular regulation of immunity in tea plants - Lu Rui; Jia-yi Su; Tao Li; Jia-miao Sun; Guang-heng Wu (Molecular Biology Reports, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

3D gravity anomaly inversion based on LinkNet - Hou-Pu Li; Rui Qi; Jia-Xin Hu; Yu-Xin Sun (Applied Geophysics, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Thiobacillus spp. and Anaeromyxobacter spp. mediate arsenite oxidation-dependent biological nitrogen fixation in two contrasting types of arsenic-contaminated soils - Yongbin Li; Lifang Guo; Rui Yang; Zhaohui Yang; Haihan Zhang; Qiqian Li; Zhiguo Cao; Xin Zhang; Pin Gao; Wenlong Gao; Geng Yan; Duanyi Huang; et al. (Journal of Hazardous Materials, 2023)

Self-assembly of Au nanocrystals into large-area 3-D ordered flexible superlattice nanostructures arrays for ultrasensitive trace multi-hazard detection - Wei Liu; Qian Li; Jiabin Wu; Weizhe Wang; Rui Jiang; Chunli Zhou; Shuangbao Wang; Xueming Zhang; Tangyou Sun; Zhimou Xu; Dingsheng Wang (Journal of Hazardous Materials, 2023)

Morphology regulation of zero-valent iron nanosheets supported on microsilica for promoting peroxymonosulfate activation - Xiangwei Zhang; Xinlin Wang; Rui Zhu; Qi Tan; Chunquan Li; Zhiming Sun (Journal of Environmental Management, 2023)

Microwave-assisted co-precipitation preparation of CuFe2O4 photo-Fenton degradation tetracycline: Characterization, efficacy, stability in complex water quality and mechanism - Xiyu Sun; Guangzhi Wang; Likun Huang; Huanzhang Feng; Simin Zhou; Rui Zhao; Dongdong Wang; Zhe Li (Journal of Environmental Chemical Engineering, 2023)

Effects of natural wax types on the physicochemical properties of starch/gelatin edible films fabricated by extrusion blowing - Yue Cheng; Xiaosong Zhai; Yuhao Wu; Cheng Li; Rui Zhang; Chanchan Sun; Wentao Wang; Hanxue Hou (Food Chemistry, 2023)

Aptasensing a class of small molecules based on split aptamers and hybridization chain reaction-assisted AuNPs nanozyme - Sai Wang; Yinglin Zhao; Rui Ma; Wenjing Wang; Ling Zhang; Jiao Li; Jianan Sun; Xiangzhao Mao (Food Chemistry, 2023)

Hovenia acerba Lindl. peduncles and seeds extracts ameliorate alcoholic liver injury by activating the Nrf2/HO-1 signalling pathway in LO2 cells and mice - Rui-fei Cheng; Meng-ke Sun; Qi-rui Hu; Zeyuan Deng; Bing Zhang; Hongyan Li (Food Bioscience, 2023)

Long-term effects of optimized fertilization, tillage and crop rotation on soil fertility, crop yield and economic profit on the Loess Plateau - Haoyu Li; Yuanhong Zhang; Yuanguang Sun; Pengzhao Liu; Qi Zhang; Xiaoli Wang; Rui Wang; Jun Li (European Journal of Agronomy, 2023)

Endogenous partial denitritation as an efficient remediation to unstable partial nitritation-anammox (PNA) process: Bacteria enrichment and superior robustness - Qiongpeng Dan; Rui Du; Tong Wang; Tiantian Sun; Xiyao Li; Qiong Zhang; Yongzhen Peng (Chemical Engineering Journal, 2023)

Long-term exposure to ambient particulate matter and kidney function in older adults - Yingxin Li; Xueli Yuan; Jing Wei; Yuanying Sun; Wenqing Ni; Hongmin Zhang; Yan Zhang; Rui Wang; Ruijun Xu; Gongbo Chen; Yuewei Liu; Jian Xu (Atmospheric Environment, 2023)

MicroRNA-588 regulates the invasive, migratory and vasculogenic mimicry-forming abilities of hypoxic glioma cells by targeting ROBO1 - Rui Yu; Rongrong Zhao; Xiaopeng Sun; Zongpu Zhang; Shaobo Wang; Xiao Gao; Zhongzheng Sun; Hao Xue; Gang Li (Molecular Biology Reports, 2023)
Background The microenvironment of hypoxia is an important factor contributing to the development of glioblastoma (GBM). MicroRNA-588 and its potential target Roundabout-directed receptor 1 (ROBO1) have been reported to promote tumor invasion and proliferation in diseases such as gastric, pancreatic and hepatocellular carcinoma, while their function in GBM and response to hypoxic states remain elusive. Methods A microarray was leveraged to identify differentially expressed microRNAs in U251 glioma cells cultured under normoxic and hypoxic conditions. The expression of miR-588 was assessed using quantitative real-time PCR (qRT‒PCR). Gain- and loss-of-function studies were used to evaluate the role of miR-588 under hypoxic and normoxic conditions. Cell invasion, migration, proliferation, and vasculogenic mimicry (VM) formation experiments were performed. The relationship between miR-588 and ROBO1 was confirmed using western blot and luciferase reporter assays. Intracranial xenograft tumor mouse models were used to study the function of miR-588 in vivo. Results The expression of miR-588 was significantly upregulated in hypoxic glioma cells relative to normoxic glioma cells. miR-588 inhibited the invasive, migratory and VM-forming abilities of glioma cells in vitro and in vivo. Mechanistically, roundabout guidance receptor 1 (ROBO1) is a direct, functionally relevant target of miR-588 in glioma. ROBO1 knockdown suppressed the expression of matrix metallopeptidase 2 (MMP2) and matrix metallopeptidase 9 (MMP9), thereby inhibiting the invasive, migratory and VM-forming abilities of glioma. Conclusions MiR-588 regulated the behaviors of hypoxic glioma cells by targeting ROBO1. miR-588 can be used as a prognostic marker for glioma and has potential implications in glioma gene therapy.

Electroacupuncture promotes remyelination and alleviates cognitive deficit via promoting OPC differentiation in a rat model of subarachnoid hemorrhage - Yingwen Wang; Xiaomin Yang; Yunchuan Cao; Xiaoguo Li; Rui Xu; Jin Yan; Zongduo Guo; Shanquan Sun; Xiaochuan Sun; Yue Wu (Metabolic Brain Disease, 2023)

Effects of single or conjoint administration of lactic acid bacteria as potential probiotics on the growth, immune responses, and disease resistance of Carassius auratus - Ruoming Li; Teng Chi; Qing Xu; Juntong Liu; Xiaofeng Shan; Rui Zhou; Jiayun Yao; Wuwen Sun; Guiqin Wang (Aquaculture International, 2023)

Channeling analysis of wavelet threshold processing based on K-means clustering algorithm - Lixiong Gan; Ming Li; Wenyuan Cai; Jian Li; Zhanglong Chen; Jian Sun; Rui Deng (Acta Geophysica, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The formation of supercritical carbon dioxide hydrothermal vents in the Okinawa Trough - Fanfan Tian; Rui Li; Guozhi Xie; Kun Wang; Lipeng Zhang; Xin Zhang; Weidong Sun (Science Bulletin, 2023)

Maternal atmospheric particulate matter exposure and risk of adverse pregnancy outcomes: A meta-analysis of cohort studies - Liangliang Ju; Lei Hua; Hanbing Xu; Changlian Li; Shu Sun; Qi Zhang; Jiyu Cao; Rui Ding (Environmental Pollution, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

Chemical composition, sources and evolution of PM2.5 during wintertime in the city cluster of southern Sichuan, China - Junke Zhang; Xiaojuan Huang; Jiaqi Li; Luyao Chen; Rui Zhao; Rui Wang; Wei Sun; Chunying Chen; Yunfei Su; Fangzheng Wang; Yawen Huang; Chaobiao Lin (Atmospheric Pollution Research, 2023)

The effect of precipitation timing on phylogenetic and functional community structure in a semi-arid steppe - Zhongling Yang; Manman Wang; Jianwen Yang; Rui Xiao; Chen Miao; Yanfeng Sun; Tong Zhang; Guoyong Li (Oecologia, 2023)

Development, characterisation, and in vitro anti-tumor effect of self-microemulsifying drug delivery system containing polyphyllin I - Xin Wang; Rui Zhang; Shu Wang; Minju Gu; Yuan Li; Xiuping Zhuang; Chao Chen; Peimin Yang; Gongling Guo; Ping Sun (Drug Delivery and Translational Research, 2023)

Effects of combined application of nitrogen, phosphorus, and potassium fertilizers on tea (Camellia sinensis) growth and fungal community - Sheng Tang; Jingjie Zhou; Wankun Pan; Tao Sun; Mengjiao Liu; Rui Tang; Zijing Li; Qingxu Ma; Lianghuan Wu (Applied Soil Ecology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)